A BAC-based physical map of Zhikong scallop (Chlamys farreri Jones et Preston). - Xiaojun Zhang (Public Library of Science (PLoS), 2011)
Zhikong scallop (Chlamys farreri) is one of the most economically important aquaculture species in China. Physical maps are crucial tools for genome sequencing, gene mapping and cloning, genetic improvement and selective breeding. In this study, we have developed a genome-wide, BAC-based physical map for the species. A total of 81,408 clones from two BAC libraries of the scallop were fingerprinted using an ABI 3130xl Genetic Analyzer and a fingerprinting kit developed in our laboratory. After data processing, 63,641 (∼5.8× genome coverage) fingerprints were validated and used in the physical map assembly. A total of 3,696 contigs were assembled for the physical map. Each contig contained an average of 10.0 clones, with an average physical size of 490 kb. The combined total physical size of all contigs was 1.81 Gb, equivalent to approximately 1.5 fold of the scallop haploid genome. A total of 10,587 BAC end sequences (BESs) and 167 markers were integrated into the physical map. We evaluated the physical map by overgo hybridization, BAC-FISH (fluorescence in situ hybridization), contig BAC pool screening and source BAC library screening. The results have provided evidence of the high reliability of the contig physical map. This is the first physical map in mollusc; therefore, it provides an important platform for advanced research of genomics and genetics, and mapping of genes and QTL of economical importance, thus facilitating the genetic improvement and selective breeding of the scallop and other marine molluscs.